PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK SAYURAN DI PASAR MODERN KOTA MEDAN - IRHAMNA MANDILI LUBIS (JURNAL ILMIAH SIMANTEK, 2020)
Population growth that continues to increase and development developments that continue to increase will have an impacton changes in land use. Changes in land use will result in a shift in land use from agricultural to non-agricultural land whichwill affect food production. The land that originally served as a place to grow crops (agriculture), has gradually changed tomulti-use-use functions. Changes from land use for agriculture to non-agricultural benefits are increasing. Initially, the mainpurpose of changing the use of agricultural land to non-agriculture was to improve the welfare of the community and thenation's economy. However, its implementation can threaten the capacity of food supply if it is not controlled. Even in thelong term, changing the use of agricultural land to non-agricultural can result in social losses. Another interesting thing is thatalthough currently vegetable products are increasingly available in various shopping places, their sales have not increasedsignificantly. Producers and marketers need to understand what consumers really want and what things influence or areconsidered during the purchase of vegetables. The behavior of consumers who buy vegetable products is interesting toresearch, about how the reasons, the types of vegetable products purchased, the number of frequency of purchases, and soon. For this purpose, it is important to conduct research on Consumer Behavior in Buying Vegetable Products in ModernMarkets. Characteristics based on age, most of them are respondents who have an age range of 26-35 years (41%). Thesecond largest percentage is adults aged 36-45 years (34%) and adolescents aged 15-25 years are in third place (25%).Overall, vegetable buyers are dominated by young mothers who are starting to pay attention to the health of their families.Most of the respondents' marital status was married 73 people (73%), while 27 people (27%) were unmarried, becauserespondents stated that people who are married must provide healthy and clean food for their families.